Choreographies of African identities : négritude, dance, and the National Ballet of Senegal - Castaldi, Francesca, 1964- (University of Illinois Press, 2006)
"Structured as a polyrhythmic ensemble, the narrative in Francesca Castaldi's Choreographies of African Identities "sounds" three interrelated interpretations of the work of the National Ballet of Senegal, each interpretation overlapping with the others as the layering of tracks in a music score." "The first interpretative track situates the work of the Ballet in a North American theater, exposing the theatrical and extra-theatrical procedures that collude in racializing the encounter between performers and audiences as that between Black dancers and White spectators." "The second line of analysis examines the work of the National Ballet in relation to Leopold Sedar Senghor's Negritude ideology and cultural politics, engaging in larger debates over African aesthetics, modernity and tradition, globalization, and cultural diversity." "Finally a third interpretative track presents the circulation of dances in the streets, discotheques, and courtyards of Dakar, drawing attention to women dancers' occupation of the urban landscape. In this context, Castaldi explores the agency of women's performance in negotiating Islamic religiosity, gender, and class identities in the dancing circle and the public arena. Taken together, the reading weaves together questions about scholarship, the cross-cultural circulation of performance, national politics, and urban youth culture. Book jacket."--Jacket